1982
DOI: 10.1007/bf00231409
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of lens transparency or its disturbances by densitometric image analysis of scheimpflug photographs

Abstract: Scheimpflug photography of the anterior eye segment with densitometric image analysis to measure lens transparency has proven its value in long-term follow-up studies of lens changes. The necessary technical conditions of the SL 45 Topcon camera guarantee high reproducibility. The technical control with respect to quality in case of repeated photography is ensured by an internal standard, the camera being equipped with a five-step scale of known density values. External standardization is done by taking the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 5 publications
1
42
0
1
Order By: Relevance
“…Implementing Scheimpflug and retroillumination digital photography with computerised analysis of lens opacities has allowed progression of cataract to be measured with great precision. [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] This method, cost effective for the large epidemiological studies, 89 is probably the best technique for recording cataract changes.…”
Section: Quantification Of Lens Opacity Measurements In Risk Factor Amentioning
confidence: 99%
“…Implementing Scheimpflug and retroillumination digital photography with computerised analysis of lens opacities has allowed progression of cataract to be measured with great precision. [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] This method, cost effective for the large epidemiological studies, 89 is probably the best technique for recording cataract changes.…”
Section: Quantification Of Lens Opacity Measurements In Risk Factor Amentioning
confidence: 99%
“…The film (Kodak TX 5063) was devel oped according to a standard method. 2 The spatial distribution of back scattering in the nucleus was measured with a modified Leitz microscope pho tometerl5 equipped with a recording device that allowed two-dimensional positioning of the measuring area with a micrometer resolution. The measuring area was 0.2 x 0.2 mm in the object plane, and the linear magni fication was 30 times.…”
Section: Lens Pho Tography and Densitometry Of The Pho Tographsmentioning
confidence: 99%
“…Shibata et al [1,2] measured the thickness of transparent lenses in Japanese and German subjects and found that the thickness of a transparent lens increased 0.02 mm per year in both groups. It was also reported that the light scattering intensities of single lens layers increased with aging [3][4][5][6][7][8][9]. From these changes, we proposed a concept for 'lens age' as an indicator of lens transparency in an individual lens [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evaluated the changes with aging of lens thickness and light scattering intensity using Scheimpflug photography [1][2][3][4][5][6][7][8][9] and the reliability of this method has been widely accepted. Shibata et al [1,2] measured the thickness of transparent lenses in Japanese and German subjects and found that the thickness of a transparent lens increased 0.02 mm per year in both groups.…”
Section: Introductionmentioning
confidence: 99%